2020
DOI: 10.1186/s12876-020-01557-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gastroscopy results among healthy people undergoing a medical checkup: a retrospective study

Abstract: Background The association of upper gastrointestinal endoscopic findings with sex, age, and Helicobacter pylori infection in asymptomatic healthy people is unclear. The aim of this study was to retrospectively determine the associations of upper gastrointestinal endoscopic findings in asymptomatic healthy people with sex, age, and H. pylori infection. Methods A retrospective study was conducted on 2923 patients from a health examination center in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…First, H. pylori-positive individuals tend to have more severe gastritis than H. pylori-negative individuals, and their proportion of peptic ulcers is also higher. 34 Endoscopic manifestations provide endoscopists with a distinct visual impact of the harmful effects of H. pylori infection. Second, RUT has become a widely used invasive method in H. pylori detection.…”
Section: Discussionmentioning
confidence: 99%
“…First, H. pylori-positive individuals tend to have more severe gastritis than H. pylori-negative individuals, and their proportion of peptic ulcers is also higher. 34 Endoscopic manifestations provide endoscopists with a distinct visual impact of the harmful effects of H. pylori infection. Second, RUT has become a widely used invasive method in H. pylori detection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the above mentioned relations, our study found an independent decreasing trend in the risk of GC among participants with increasing time difference from the first reported diagnosis of chronic gastritis. This may be attributed mainly to the following: a) respondents without reported diagnosis of chronic gastritis may not necessarily be free from the disease since a large part of them had never underwent gastro-endoscopic examinations; 36 , 37 b) people with functional gastrointestinal disorders are more likely to seek help from clinicians and thus have greater chances to have earlier diagnosis or even misdiagnosis of chronic gastritis. 38–41 Compared with chronic gastritis, diagnosis of H. pylori infection is much more convenient, cheaper and popular in China.…”
Section: Discussionmentioning
confidence: 99%
“…Carabotti et al found no difference in dyspeptic symptoms between patients with antrum‐restricted gastritis and those with pangastritis ( P > 0.05) 48 . Huang et al reported that 99.59% of the asymptomatic subjects who underwent gastroscopy had abnormal results, and the majority of them (95.11%) had chronic gastritis 49 …”
Section: Clinical Issues and Statementsmentioning
confidence: 99%
“…48 Huang et al reported that 99.59% of the asymptomatic subjects who underwent gastroscopy had abnormal results, and the majority of them (95.11%) had chronic gastritis. 49 H. pylori gastritis is the predominant form of chronic active gastritis in young and middle-aged patients. 15 Among elderly patients, in addition to H. pylori infection, NSAIDs, long-term bile reflux, and other physical and chemical injuries may lead to chronic gastritis in the elderly, and there are more symptomatic patients compared to young and middle-aged patients.…”
mentioning
confidence: 99%